Patriotism as the subject of discursive practices in Russia - Grigoryevich Volkov, Yury; Vladimirovna Vereshchagina, Anna; Vladimirovich Lubsky, Anatoly; Viktorovich Gubarev, Ivan; Olegovna Vagina, Viktoriya (International Journal of Engineering and Technology, 2018)
Discourses of the patriotism in Russia represent presentations of its study results in the framework of such scientific disciplines, as philosophy, history, political science, sociology and psychology. Within the framework of these disciplines, the patriotism is studied, taking into account various paradigmatic preferences, first, ontological, axiological, identification and behavioural content. The diversity of the paradigmatic foundations of research practices generates in the discourse the most diverse ideas about the patriotism in Russia. These representations, filled with the specific content, are, as a rule, of disciplinary unilateral and paradigmatic limited nature. The conceptual comprehension of the patriotism in Russia, as an integral social reality presupposes the development of a multidimensional methodological construct of its holistic scientific study.